DIETARY INFLUENCE OF SYSTOLIC AND DIASTOLIC BLOOD PRESSURE IN THE TWINSUK COHORT. (April 2021) - Louca, Panayiotis; Berry, Sarah E.; Spector, Timothy D.; Padmanabhan, Sandosh; Menni, Cristina
Abstract : Objective: Hypertension is a major modifiable risk factor for cardiovascular morbidity and mortality. Clinical and population-based studies show that several dietary components affect blood pressure and modification of these nutritional factors provide an important strategy to control blood pressure and reduce rates of hypertension. In this study, we examined the association between different nutrient intake and blood pressure in a cohort of adult twins. Design and method: We included 2252 adults from the TwinsUK registry not on hypertensive treatments with concurrent clinical blood pressure measurements. All subjects completed a Food Frequency Questionnaire facilitating estimated intake of 45 nutrients. Linear mixed models were used to investigate nutrient intake on systolic and diastolic blood pressure adjusting for age, gender, BMI and family relatedness. A Bonferroni correction was applied for multiple testing. A backward linear regression was then used to determine independently associated nutrients. Results: We identified 24 nutrients significantly associated with blood pressure after adjusting for covariates and multiple testing (Figure.1). Of those nutrients, 21 were negatively associated with SBP, 14 were negatively associated with DBP and one was positively associated with DBP. Among those with the greatest association with SBP were: riboflavin (Beta(SE): -1.39(0.34), p = 1.11x10-6), manganese (-0.55(0.2), p = 1.25x10-4) and maltose (-0.35(0.13), p = 1.35x10-4). Intake of manganese (-0.32(0.14), p = 3.85x10-4), vitamin e (-0.13(0.05), p = 3.12x10-4) and polyunsaturated fats (-0.09(0.04), p = 5.76x10-4) had the largest negative correlation with DBP, while, alcohol intake showed a positive correlation with DBP (0.03(0.01), p = 4.16x10-4). From the multivariable model, the following six nutrients were independently associated with systolic blood pressure, explaining 22% of the variance: vitamin b12 (-0.19), biotin (- 0.12), total fat (- 0.13), starch (- 0.03), total sugars (-0.04) and energy intake (-0.01). Five nutrients were independently associated with diastolic blood pressure and explained 14% of the variance, those were biotin (-0.08), magnesium (-0.01), energy intake (-0.00), carotene (-0.00) and alcohol (-0.06). Figure. No caption available. Conclusions: Our findings confirm current understanding and extend the panel of dietary nutrients implicated in blood pressure regulation. Our new findings of dietary factors that affect blood pressure after validation offer additional diet and lifestyle approaches in hypertension prevention and management.